Hypertensive Disorders in Pregnancy Are Associated With Congenital Heart Defects in Offspring: A Systematic Review and Meta-Analysis - Senmao Zhang; Senmao Zhang; Xing Qiu; Tingting Wang; Letao Chen; Letao Chen; Jinqi Li; Jinqi Li; Jingyi Diao; Jingyi Diao; Yihuan Li; Yihuan Li; et al. (Frontiers in Cardiovascular Medicine, 2022)
BackgroundAlthough research indicates an association between hypertensive disorders of pregnancy (HDP) and congenital heart defects (CHDs) in offspring, consistency is still lacking. Therefore, we aimed to synthesize the updated published epidemiologic evidence to estimate the association of maternal HDP with the risk of total CHDs and its phenotypes in offspring.MethodsA systematic search of Web of Science Database, PubMed, and Embase were searched from inception through April 30, 2021 based on a preprepared protocol, and the reference lists were also manually searched. The combined risk estimates were calculated using either the fixed-effect models or random-effect models. Possible heterogeneity moderators were detected by subgroup, sensitivity analyses, and Galbraith plot.ResultsTwenty-four studies involving 477,839 CHDs cases among 40,394,699 participants were included in our meta-analysis. Mothers who had HDP exposure were significantly associated with an increased risk of total CHDs compared with non-exposure. When maternal HDP exposure was further subdivided into pre-eclampsia (OR = 1.79, 95% CI: 1.50–2.13), gestational hypertension (OR = 1.16, 95% CI: 1.02–1.31), and chronic hypertension (OR = 1.68, 95% CI: 1.49–1.89), a significantly increased risk of total CHDs were still presented. Furthermore, a statistically significant increased association was found between maternal HDP exposure and most CHD phenotypes. Besides, relevant heterogeneity moderators have been identified by subgroup and sensitivity analyses.ConclusionOur study suggested that maternal HDP exposure may be associated with an increase in the risk of CHDs in offspring. These findings highlight the need for greater surveillance of pregnant women with HDP exposure to allow early prevention that may be good for reducing the risk of CHDs in offspring.Clinical Trial Registration[www.ClinicalTrials.gov], identifier [CRD42021268093].